The Examining Philosophical Foundation of Children Language Development Program Based on 2013 Curriculum - Astuti S.Pd, M.Hum., Wili (Muhammadiyah University Prss, 2019)
The theory of early childhood education aims to expose and research the complexities of child education. The goal of the study was to define the philosophy of the Language Development Program based on the 2013 Early Childhood Education Curriculum. Data collection techniques in this study used direct observation and recording methods in the Lesson Plan in Language development program based on 2013 ECE curriculum, based on predetermined categories. Data sources in this study were all information written in the children's language development program which was prepared in accordance with the 2013 curriculum. The data will be analyzed by Qualitative content analysis. The finding led to the discovery of the philosophical foundation of children language development program which are dominated by Progresivism.